2018
DOI: 10.1108/jaoc-04-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

The adoption and benefits of life cycle costing

Abstract: Purpose Although life cycle costing (LCC) is well established in theory and practice, little is known about the conditions of its adoption and its impact on the achievement of cost-management goals. Therefore, this paper aims to analyze the adoption and benefits of LCC. Design/methodology/approach The analyses are based on questionnaires collected from a survey of German firms. Findings The results demonstrate that the extent of LCC adoption is positively associated with the extent of guarantee and warrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
2
22
0
2
Order By: Relevance
“…More specifically, through data displays that are widely disseminated, LCC results can concretize the lifecycle idea, enhance individuals' perception of the scope of company responsibility over the lifecycle, visualise the changing incentive structure in terms of costs and revenue and highlight the importance of services (Paper V). These findings are supported by the work of Knauer and Möslang (2018) who, based on a survey of German companies, found that companies have cognition related goals when adopting LCC such as increased cost awareness and transparency, and cost driver identification. Moreover, the companies perceived that they obtain many benefits from using LCC in relation to those goals (ibid.…”
Section: Alignment With the Changing Incentive Structuressupporting
confidence: 53%
See 4 more Smart Citations
“…More specifically, through data displays that are widely disseminated, LCC results can concretize the lifecycle idea, enhance individuals' perception of the scope of company responsibility over the lifecycle, visualise the changing incentive structure in terms of costs and revenue and highlight the importance of services (Paper V). These findings are supported by the work of Knauer and Möslang (2018) who, based on a survey of German companies, found that companies have cognition related goals when adopting LCC such as increased cost awareness and transparency, and cost driver identification. Moreover, the companies perceived that they obtain many benefits from using LCC in relation to those goals (ibid.…”
Section: Alignment With the Changing Incentive Structuressupporting
confidence: 53%
“…Gluch et al (2018) discuss two such uses: to legitimize an alreadypreferred option and to facilitate a discussion about long-term issues such as renovation. Knauer and Möslang (2018) verified that companies have both cognitionrelated and result-oriented cost-management goals when using LCC. Facilitating discussions and improving cognition have similarities to the use presented in Chapter 5.4 of "understanding and overcoming challenges".…”
Section: Implications On Future Methodological Lcc Developmentmentioning
confidence: 82%
See 3 more Smart Citations